Brace yourself - Abu Bakar, Noraini (2021)
Fake braces and fake practitioner has become more rampant nowadays. This talk was aimed to create awareness amongst the teenagers, especially for secondary school students from SMK Taman Melati as part of Dental4Youth:Dental4U programme, as organised by final year students of Diploma Bahasa Inggeris Komunikasi Professional UiTM Melaka.